A comprehensive geospatial assessment of seagrass distribution in India. (1st June 2018) - Geevarghese, Gejo Anna; Akhil, B.; Magesh, G.; Krishnan, P.; Purvaja, R.; Ramesh, R.
Abstract: The study deals with the first comprehensive spatial distribution and area estimate of seagrass patches of India with a standardized methodology. Seagrass patches are mainly located in Palk Bay – Gulf of Mannar (Tamil Nadu), Gulf of Kachchh (Gujarat), Chilika Lake (Odisha) and Islands of Andaman & Nicobar and Lakshadweep. Medium resolution satellite images of Landsat 8 OLI were subjected to radiometric, atmospheric and water column correction prior to digital classification and contextual editing. Total estimated seagrass area amounts to 516.59 km 2 of which Palk Bay and Gulf of Mannar of Tamil Nadu together contribute to 398.81 km 2 . Overall classification accuracy for the six sites studied, ranged between 64% (Lakshadweep Islands) and 83.5% (Palk Bay). This suggests that for surveillance studies of homogeneous seagrass meadows with low interspersion of other benthic units such as corals, seaweeds etc., digital mapping using medium resolution data sets with mandatory attenuation correction procedures is suitable. The results of this study and the related area statistics were accepted as a baseline at national level for the delineation of Ecologically Sensitive Areas (ESA) and in the formulation of its conservation strategies. For a cursory appraisal of the status of major seagrass regions, a matrix representation of its locational occurrence and habitat characteristics is provided. Highlights: First comprehensive spatial estimate of seagrass meadows in India is provided. Landsat 8 OLI images classified after performing attenuation correction algorithms. Spatial output and area estimate can aid in formulation of conservation strategies.